Information use on Decision-making Process of Administrative Staff of Federal University of Agriculture Abeokuta, Ogun State, Nigeria - Unegbu, Vincent E. (Information Management and Business Review, 2013)
Information is vital in decision making; and bad decisions most of the times are as a result of lack of adequate information. This research examined the administrative staff’s use of information in their decision making process in Federal University of Agriculture, Abeokuta. The descriptive survey, total enumeration technique, and a well-structured questionnaire were used to obtain data. Most of the administrative staff members were fully aware of how the use of information aids in administrative decisions. The most frequently consulted information sources were internal memo, minutes of meeting, schedules of meeting, past conference papers and dictionaries. The reasons for administrative staff’s use of information were according to confronting issues like scheduling appointments, calling up meetings, and recruiting new staff. The use of mobile phones by administrative staff should be encouraged since the administrators could receive messages anywhere and at any point in time to make both individual and administrative decisions.